A dynamic ductile failure analysis of shell structures using a nonlocal XFEM method with experimental validation. (September 2018) - Wu, C.T.; Ma, N.; Guo, Y.; Hu, W.; Takada, K.; Okada, H.; Saito, K.
Highlights: A XFEM shell formulation based on phantom-node method is applied to a fully integrated first-order shear-deformable shell element. A continuous-discontinuous approach is adopted for the XFEM dynamic ductile failure analysis in shells. A nonlocal modeling procedure is developed for XFEM shells for damage-induced strain localization problem. A numerical calibration for regularization limiter in the proposed nonlocal modeling procedure is presented. The present method is both numerically and experimentally validated. Abstract: This paper presents a finite element continuous-discontinuous approach for the dynamic ductile failure analysis of shell structures. The continuum damage model based on continuous displacements is used in the continuous stage to describe the diffuse micro-cracking in ductile failure of high-strength steel before a macro-crack is formed. In the context of a fully integrated shear deformable shell formulation, a nonlocal modeling procedure based on a projection of mid-plane reference surface is introduced to regularize the element-wise strain fields induced by the continuum damage model. In the discontinuous stage, an incorporation of velocity discontinuities in shell finite elements is pursued by XFEM method when the damage variable exceeds a critical value and the transition from a continuous to a discontinuous model is permitted. A phantom-node approach is employed in the XFEM method to simplify the numerical treatment of velocity discontinuities in the shell finite element formulation. Several numerical benchmarks are examined using the explicit dynamics analysis and the results are compared with the experimental data to demonstrate the effectiveness and accuracy of the proposed method.